Hubungan Transformational Leadership Serta Peran Exchange Norm dan Communal Norm Terhadap Employee Voice Dalam Industri Swasta di Jabodetabek [Relationship Between Transformational Leadership and the Role of Exchange Norm and Communal Norm with Employee Voice in Private Industry in Jabodetabek] - P.W., Maria Yolandita; Barry, Rinto Rain (Feedforward: Journal of Human Resource, 2021)
This study aims to determine whether transformational leadership, exchange norm, and communal norm have a positive relationship with employee voice. This study was shown to private employees of the banking industry with 133 respondents consisting of 98% male respondents and 2% female respondents. The instrument used for data collection is a questionnaire, which consists of 13 indicators. Testing of the questionnaire was carried out by means of a validity test which resulted in sig < Î± (0.000 < 0.05) and a reliability test which resulted in Cronbach's Alpha > 0.7. Furthermore, the tool used in analyzing the data is IBM SPSS 25. The results of this study reveal that transformational leadership has a positive relationship with exchange norm, transformational leadership has a positive relationship with communal norm, transformational leadership has a positive relationship with employee voice, norm exchange has a positive relationship with employee voice, and communal norm have a positive relationship with employee voice.